Long-term Follow-up of Cheilectomy for Treatment of Hallux Rigidus. Issue 4 (16th October 2019) - Sidon, Eliezer; Rogero, Ryan; Bell, Timothy; McDonald, Elizabeth; Fuchs, Daniel; Shakked, Rachel J.; Daniel, Joseph N.; Pedowitz, David I.; Raikin, Steven M.
Category: Midfoot/Forefoot Introduction/Purpose: Hallux rigidus (HR) is the most common arthritic condition in the foot. The surgical treatment options involve cheilectomy, interposition arthroplasty, or arthrodesis of the 1st metatarsophalangeal joint (MTPJ). 1st MTPJ cheilectomy has been shown to produce satisfactory results in retrospective studies. Previous retrospective studies have reported up to 97% good to excellent results and 92% success in pain relief and function. The results of cheilectomy for higher grades of HR are less favorable, with conversion rates ranging from 25 to 56%. The purpose of this study is to evaluate the long-term functional results and survivorship of cheilectomy for treatment of HR. Methods: This is a retrospective study investigating the long-term results of cheilectomy for treatment of HR, performed by 3 fellowship-trained foot & ankle surgeons. Patient demographics, diagnoses, medical comorbidities, and physical examination notes were collected from our electronic medical record system. A fellowship-trained foot & ankle surgeon not involved in any patient's care evaluated preoperative radiographs and assigned a HR grade (1-3, Hattrup & Johnson). All patients without available preoperative radiographs or who underwent concomitant procedures other than cheilectomy were excluded. A questionnaire was administered via email or telephone that included questions regarding pain recurrence following surgery, current functional status, satisfaction with surgery, shoe wear limitations, and details about need for further intervention of the great toe, including MTPJ injections or revision procedures. Cox regression analysis was performed to investigate patient factors contributing to lack of pain recurrence, which was treated as survival time. Results: One-hundred sixty-five patients (169 cases) were included, with a mean follow-up time of 6.6 years (range, 5.0-10.9 years). Most cases (118, 70%) were grade 2, with 30 (18%) grade 1 and 21 (12%) grade 3 cases. One-hundred forty-three of 169 (85%) cases experienced pain relief in the immediate period following surgery. The satisfaction rate was 69% (117/169), and the overall pain-free survival rate was 68%, without any significant difference between arthritic grades. In 75% of cases with pain recurrence, pain returned within the first 2 years following surgery. Nine cases (5%) required a revision procedure at a mean postoperative 3.6 years (range, 1.6-7.4 years). Cox regression analysis revealed older age (p=.062) and male sex (p=.058) to be marginally related to having less pain recurrence. Conclusion: Our study supports the use of cheilectomy for treatment of HR as a reliable procedure with favorable results. At long-term follow-up, patients who underwent cheilectomy had a low revision surgery rate and a moderately low rate of pain recurrence, with most pain recurrence occurring within the first 2 years. These results were not influenced by the preoperative arthritic grade, as long as the cheilectomy was performed on patients with no mid-range pain. These results can be used in treatment selection and anticipatory guidance for patients presenting with HR.